Fabrication of Loose Nanofiltration Membranes with High Rejection Selectivity between Natural Organic Matter and Salts for Drinking Water Treatment - Zhihai He; Kunpeng Wang; Yanling Liu; Ting Zhang; Xiaomao Wang (Membranes, 2022)
Loose nanofiltration (LNF) membranes with a molecular weight cut-off (MWCO) of about 1000 Da and high surface negative charge density have great application potential for drinking water treatment pursuing high rejection selectivity between natural organic matter (NOM) and mineral salts. This study was conducted to exploit the novel method coupling non-solvent induced phase separation (NIPS) and interfacial polymerization (IP) for the preparation of high-performance LNF membranes. A number of LNF membranes were synthesized by varying the polyethersulfone (PES) and piperazine (PIP) concentrations in the cast solution for the PES support layer preparation. Results showed that these two conditions could greatly affect the membrane water permeance, MWCO and surface charge. One LNF membrane, with a water permeance as high as 23.0 ± 1.8 L/m2/h/bar, when used for the filtration of conventional process-treated natural water, demonstrated a rejection of NOM higher than 70% and a low rejection of mineral salts at about 20%. Both the mineral salts/NOM selectivity and permselectivity were superior to the currently available LNF membranes as far as the authors know. This study demonstrated the great advantage of the NIPS–IP method for the fabrication of LNF membranes, particularly for the advanced treatment of drinking water.